Hubungan Antara Pendidikan Karakter dengan Kecerdasan Sosial Siswa Kelas V SDN Gugus V Kecamatan Cakranegara Tahun Pelajaran 2018/2019 - Ni Made Dwi Trisnayani; Khairun Nisa; Abdul Kadir Jaelani (Indonesian Journal of Elementary and Childhood Education, 2020)
This research aims to identify the correlation between character education and social intelligence of fifth grade students of SDN Cluster V District Cakranegara academic year 2018/2019. The research design used is a quantitative approach to the type of correlational research. The population in this study were all fifth-grade students of SDN Cluster V Cakranegara subdistrict, amounting to 189 students. The sampling technique uses proportional random sampling technique so that a sample of 127 students is obtained. The data collection method used was a questionnaire. Data were analyzed by prerequisite test and hypothesis test. Hypothesis testing uses the product moment correlation formula. The results showed that: (1) Student character education in terms of aspects of tolerance, friendly/communicative, and social care as a whole gained an average score of 77 which was included in the sufficient category; (2) Social intelligence of students in terms of aspects of social sensitivity, social insight, and social communication as a whole obtained an average score of 74 included in both categories; (3) There is a significant relationship between character education and social intelligence of fifth grade students at SDN Cluster V Cakranegara subdistrict in the academic year 2018/2019 based on the results of hypothesis testing at N = 127 with a significance level of 5%, the results obtained are 0.740 (rtest)> 0.1743 (rtable), which is included in the level of relationship with a high category.